Effect of ethanol extract and infusion of Aloysia triphylla and Matricaria chamonilla on strains of Prevotella intermedia - Condori, Katya; Apaza, Mariela; Padilla-Cáceres, Tania (Revista Acciones Médicas, 2022)
Objective: to evaluate the inhibitory in vitro effect of the ethanolic extract and infusion of Aloysia triphylla vs Matricaria chamonilla on the strains of Prevotella Intermedia. Methods: Bacterial susceptibility tests were performed on strains of Prevotella intermedia with disks embedded with ethanolic extracts and infusions of Aloysia triphylla and Matricaria chamonilla at the concentrations of 25%, 50%, 75% and 100% respectively, chlorhexidine was used as a positive control to 0.12% and as a negative control the distilled water, evaluating the inhibition zones at 24 h and 48 hours. Results: the best inhibitory effect occurs with the treatment of 100% ethanolic extract of Matricaria chamonilla at 24 hours, with an inhibitory halo of 12.53 mm in relation to the treatment with 100% ethanolic Aloysia triphylla extract at 24 hours, whose inhibitory halo was 11.48 mm. The smallest effect of the inhibition halo was obtained with the 25% Aloysia triphylla infusion treatment at 48 hours with 6.24 mm. Conclusions: all treatments have an inhibitory in vitro effect on Prevotella intermedia, and at a higher concentration of the treatment, greater effectiveness. Likewise, treatments with ethanolic extract and Matricaria chamonilla infusion have a greater inhibitory effect in relation to the corresponding treatments of Aloysia triphylla both at 24 and 48 hours. And finally, the inhibitory effect of all treatments diminishes after 48 hours.
Keywords: inhibitory effect; Matricaria chamonilla; Aloysia triphylla; Prevotella intermedia